Erectile dysfunction and associated factors among patients with diabetes attending follow-up at a public hospital, Harar, Eastern Ethiopia. A cross-sectional study design - Gobena, Matebu Bekele; Abdosh, Tekabe; Dheresa, Merga; Dechasa, Deribe Bekele (Frontiers in Endocrinology, 2023)
Background: The global prevalence of erectile dysfunction among diabetic patients is high. It is the most underestimated problem but has a great physical, psychological, and social impact on the individual with the disease, family and society in general. Thus, this study is aimed at assessing the magnitude of erectile dysfunction and associated factors among diabetic patients attending follow up at Public Hospital, Harar, and Eastern Ethiopia. Methods: Facility based cross sectional study was conducted on selected 210 adult men diabetic patients attending follow-up at Public Hospital, Harar, Eastern Ethiopia from February1 – March 30, 2020. Simple random sampling was used to select study participants. Pre-tested interviewer administered structured questionnaire was used to collect the data. The data was entered to Epi-data version 3.1 and exported to SPSS version 20 for analysis. Bivariate and multivariate binary logistic regression were done and a P-value of <0.05 was taken as statistical significant. Result: A total of 210 adult men diabetic patients participated in the study. The overall magnitude of erectile dysfunction was 83.8%, with 26.7% suffering from mild, 37.5% mild to moderate, 29% moderate and 6.8% severe erectile dysfunctions. Age 46-59years (AOR: 2.560, 95%CI (1.73, 6.53)), age > 60years (AOR: 2.9, 95%CI (1.48, 5.67)) and poor glycemic control (AOR: 2.140(CI 1.9, 7.44) were significantly associated with erectile dysfunction among diabetic patients. Conclusion: The present study revealed high magnitude of erectile dysfunction among diabetic population. The age categories of 46–59, >60 and having poor glycemic control were the only variables significantly associated with erectile dysfunction. Thus, routine screening and management for erectile dysfunction in diabetic patients should be part of routine medical care particularly for adult male patients and those with poor glycemic control.